Microclimate Analysis of Tree Canopies and Green Surface Combinations for Urban Heat Island Mitigation in Los Angeles and Phoenix - Shaobo Yang; Pablo La Roche (Buildings)
This research addresses the critical issue of urban heat islands (UHI), in which urban areas experience significantly higher temperatures than their surroundings, adversely affecting human comfort and well-being. Focusing on Inglewood, a city neighboring Los Angeles, California, and Phoenix, Arizona, this study uses a comprehensive methodology involving microclimate analysis-based Universal Thermal Climate Index (UTCI) calculations to assess the impact of horizontal green surfaces and different levels of tree canopies on outdoor thermal stress mitigation. Phoenix was selected due to its hyper-arid desert climate, providing a contrasting context to assess the effectiveness of green infrastructure under extreme heat conditions. The results demonstrate that these interventions effectively reduce strong and moderate heat stress levels (32 °C < UTCI < 38 °C and 26 °C < UTCI < 32 °C); the model with maximum tree canopy achieved an 18.48% reduction in strong heat stress in Inglewood, while combined interventions led to a maximum reduction of 18.92%. However, the findings also reveal that under extreme heat conditions, particularly in hyper-arid environments such as Phoenix, the interventions may have a limited effect, with localized increases in extreme heat stress attributed to microclimate dynamics, reduced vegetation cooling efficiency, and modeling limitations. Despite these challenges, the overall reduction in average UTCI values underscores the potential of integrated green infrastructure strategies for mitigating urban heat stress. This study provides urban planning strategies for integrating these interventions to create more sustainable and resilient urban environments, supporting policymakers and urban planners in their efforts to reduce the effects of UHI.